TANGGAPAN IKAN PATIN (Pangasius suschi) DAN IKAN LELE (Clarias batracus Linn) TERHADAP BAU UMPAN YANG BERBEDA - Bustari, Bustari; Hindriyani, Alit (Jurnal Perikanan dan Kelautan, 2007)
In order to increase the fishing production, several efforts have been conductedand one of them is using the chemically attracted bait. To understand theeffectiveness of bait odor in attracting the fish, a study on the response ofPangusius sutchi and (lands hatracus Linn toward various bait odors has beenconducted in Pekanbaru, from 12 to 19 July 2005. This study aims to understandthe ability of fishes in detecting the odors. Three treatments were applied. The fishwere feed on chicken intestine with 3 decayed levels, namely fresh intestine,intestine that was kept for I day period and intestine that was kept for 2 daysperiod. Position/distance between the fish and the bait were noted. Result shownthat fresh chicken (U1) intestine was the most preferred by cat fish (P. sulchi),while intestine that was kept for I day period (U2) was the most preferred by catfish (C. hatracus). Chicken intestine that was kept for 2 days period (U3),however, was not preferred by both type of fishes. Based on the data obtained, itcan be concluded that cat fish (P. suichi), and cat fish (C. Indiums) are able todetect bait with different odors.